In vitro ruminal fermentation of diets containing wheat straw and date pits as forage - Lakhdara N.; Ranilla M.J.; Tejido M.L.; Bererhi E.H.; Carro M.D. (Feeding and management strategies to improve livestock productivity, welfare and product quality under climate change, 2013)
The aim of this study was to analyze the effect of partial replacement of wheat straw (WS) by date pits (DP) in diets with different forage:concentrate (F:C) ratio. Three feeds [WS, DP and a commercial concentrate (CON)] were used to formulate six diets according to a 3 × 2 factorial arrangement of treatments (3 F:C ratios and 2 forage sources). The diets had F:C ratios of 100:0, 80:20 (80) or 60:40 (60) with either WS or a 80:20 WS:DP mixture (MIX) as forage, and were designated as WS (100% WS), 80WS, 60WS, MIX, 80MIX and 60MIX. Samples (500 mg) of each diet were incubated with 50 ml of buffered rumen fluid at 39ºC. Final pH, production of volatile fatty acids (VFA), total gas and methane, NH3-N concentration and organic matter apparently fermented (OMAF) were determined after 24 h. The neutral detergent fibre (NDF) content of WS and DP was 71.1 and 86.5% (dry matter basis), but NDF lignification was greater for DP (26.7% of NDF) than for WS (15.3% of NDF). Compared with WS, the ruminal fermentation of the MIX diet resulted in greater (P<0.05) butyrate proportions (11.7 vs. 14.0%) and lower (P<0.05) gas production (2768 vs. 2588 μmol) but there were no differences (P>0.05) in the rest of the fermentation parameters. For both forages (WS and MIX), increasing the proportion of CON in the diet increased (P<0.05) the production of gas and total VFA, the molar proportion of butyrate and the OMAF. There were no differences (P>0.05) between 80WS and 80MIX diets in any fermentation parameter. Compared with 60WS diet, the fermentation of 60MIX diet resulted in greater production of total VFA (3061 vs. 3264 μmol), but no differences were detected in the rest of the parameters measured. The final pH, methane production and NH3-N concentrations ranged between 6.91 and 7.00, 434 and 516 μmol, and 330 and 359 mg/L, respectively, with no differences (P=0.059 to 0.121) among diets. The results indicate that WS can be replaced by DP at 20% of the forage portion of the diet without any detrimental effect on ruminal fermentation. Furthermore, in diets with 60:40 F:C ratio, incorporating DP resulted in greater VFA production. If this result is confirmed in vivo, it would be of great interest in sheep practical feeding.
14. International Seminar of the Sub-Network on Nutrition of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2012/06/15-17, Hammamet (Tunisia)